Faktor-Faktor yang Mempengaruhi Keputusan Pembelian pada Perusahaan Jasa (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Every company must be prepared to face difficulties and competition due to intense competition in the rapidly growing business world, especially in the transportation and freight forwarding industry. Businesses must create marketing strategies that target customer needs if they want to influence their purchasing decisions. The formulation of the problem in this study is how the influence of digital marketing strategies, word of mouth, and service quality on purchasing decisions both simultaneously and partially.  The purpose of this study is to determine the influence of digital marketing strategies, word of mouth, and service quality on purchasing decisions. This research was conducted at PT. Dwi Asri Bali in Denpasar. The population is all consumers. The number of samples in this study was 95 people, determined using accidental sampling technique and tested using multiple linear regression analysis techniques. The results of this research show that digital marketing strategies have a partially positive and significant effect on purchasing decisions. Word of mouth has a positive and partially significant effect on purchasing decisions. Service quality has a partially positive and significant effect on purchasing decisions. Digital marketing strategy, word of mouth and service quality simultaneously have a significant effect on purchasing decisions.